Influence of two levels of feeding and management systems on feed intake and growth performance of female Murrah buffalo calves - SINGH, JAGATJIT; SINGH, RAJINDER; YADAV, R S (The Indian Journal of Animal Sciences, 2012)
A study was conducted up to 6 months on 20 female Murrah buffalo calves (with average initial age of 10.50 months and body weight of 87.4 kg) at the animal farm of CCSHAU, Hisar during winter and summer to find out the effect of enhanced feeding and modified management on growth performance of female buffalo calves. Each group of 5 calves was allotted to 1 of the 4 treatments, viz. routine management and routine feeding (T1), routine management and enhanced feeding (T2), modified management and routine feeding (T3), modified management and enhanced feeding (T4). The analysis of variance revealed that there is no significant difference in average daily body weight gain between treatments. However, it was slightly higher in T2 and T4 as compared to T1 and T3 revealing that even higher protein intake supported growth equivalent to normal feeding levels under improved management practices in different seasons.